Aggregation-induced emission of 4-formyl-3-hydroxybenzoic acid for the ratiometric fluorescence detection of tetracycline antibiotics. (January 2022) - Sun, Pengyue; Yang, Diya; Li, Jing; Zhang, Yaodong
Abstract: In this work, 4-formyl-3-hydroxybenzoic acid (FHBA), which does not contain a large conjugated ring structure, exhibited aggregation-induced emission (AIE) in aqueous solvents. On this basis, FHBA and a metal-organic framework material (i.e., ZIF-8) form into a complex (FHBA@ZIF-8), which presents the AIE characteristics of FHBA. Then, lanthanide metal (i.e., Eu 3+ ) coordinates with guanosine 5′-monophosphate disodium (GMP) salt to synthesize a coordination polymer (LnCP), which combines with FHBA@ZIF-8 do afford a novel double-emitting fluorescence probe (FHBA@ZIF-8@Eu-GMP, FZE) for tetracycline antibiotics (TCAs). TCAs coordinate with Eu 3+ and act as antenna ligand. Thus, an "antenna effect" comes into being and effectively enhances the emission intensity of Eu 3+ at 616 nm. Moreover, the UV–vis spectra of TCAs largely overlap with the excitation spectrum of FHBA, resulting in an inner filter effect (IFE) and quenching of blue-green fluorescence from FHBA molecules at 473 nm. The ratio of fluorescence signal (F616 /F473 ) showed a good linear relationship with the concentration of tetracycline hydrochloride (TC) in the range of 0.1–200.0 μM, and the detection limit was 60 nM (S/N = 3). This fluorescence probe can also effectively respond to oxytetracycline hydrochloride (OTC) and chlortetracycline hydrochloride (CTC). The probe was applied to determine TC in milk, and the recoveries ranged from 94.0% to 101.4%, indicating the application potential of this method. This study provides a novel idea for the construction of ratiometric fluorescence sensing platforms and shows the application potential of the AIE effect of FHBA. Graphical abstract: Image 1 Highlights: 4-formyl-3-hydroxybenzoic acid exhibits aggregation-induced emission. A novel double-emitting fluorescence probe of tetracycline antibiotics was prepared. Double fluorescence emissions at 473 and 616 nm serve as detection signals. The novel sensing mechanism is based on inner filter and antenna effects.